2022
DOI: 10.3389/fevo.2021.783770
|View full text |Cite
|
Sign up to set email alerts
|

Rain Forest Fragmentation and Environmental Dynamics on Nosy Be Island (NW Madagascar) at 1300 cal BP Is Attributable to Intensified Human Impact

Abstract: Madagascar houses one of the Earth’s biologically richest, but also one of most endangered, terrestrial ecoregions. Although it is obvious that humans substantially altered the natural ecosystems during the past decades, the timing of arrival of early inhabitants on Madagascar as well as their environmental impact is still intensively debated. This research aims to study the beginning of early human impact on Malagasy natural ecosystems, specifically on Nosy Be island (NW Madagascar) by targeting the sedimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 96 publications
0
3
0
Order By: Relevance
“…The Rodrigues Island climate record has become a record of choice, taken as likely indicative of Madagascar's climate history by other studies of Madagascar's megafaunal population dynamics (e.g. Broothaerts et al, 2023;Domic et al, 2021;Hansford et al, 2021;Hixon et al, 2021Hixon et al, , 2022Reinhardt et al, 2022).…”
Section: Anjohibe and Rodrigues Island Paleoclimate Comparisonmentioning
confidence: 99%
“…The Rodrigues Island climate record has become a record of choice, taken as likely indicative of Madagascar's climate history by other studies of Madagascar's megafaunal population dynamics (e.g. Broothaerts et al, 2023;Domic et al, 2021;Hansford et al, 2021;Hixon et al, 2021Hixon et al, , 2022Reinhardt et al, 2022).…”
Section: Anjohibe and Rodrigues Island Paleoclimate Comparisonmentioning
confidence: 99%
“…This population seems to be related to the westward Austronesian expansion that had developed maritime trade and agricultural practices based on rice cultivation in the region from 1,250 yr BP onwards [36]. Correspondingly, human impact with an increase of anthropogenic burning has been recently suggested on the near-by Malagasy Nosy Be Island from 1,300 yr BP onwards [37]. Our new data from Lake Mahasarika combined with previously published data from Lake Maudit show very low occurrences of fires prior to 1,100 yr BP (Figure 4).…”
Section: Discussion (A) the Period Prior To Permanent Human Settlemen...mentioning
confidence: 93%
“…The available demographic studies for Northern Madagascar showed that all mammals, birds, amphibians, and non-avian reptiles ranging from Nosy Be to the Loky-Manambato region exhibited a signature of a population size change (expansion or decline) pre-dating the Late Holocene, supporting major environmental changes in the region long before humans impacted these ecosystems. Maharika (this study) from Northern Madagascar and L. Amparahibe [37] from Northwest Madagascar. e Black curve represents the number of radiocarbon dates performed on archaeological samples obtained from an archaeological data synthesis [8].…”
Section: Discussion (A) the Period Prior To Permanent Human Settlemen...mentioning
confidence: 96%
“…There are clear indications that the vegetation cover of Madagascar has undergone drastic changes over the past millennium with a general decline in forest cover that has been linked to anthropogenic impacts (Gasse & Van Campo, 2001; Joseph & Seymour, 2020; Joseph et al., 2021; McConnell & Kull, 2014; Reinhardt et al., 2022). We therefore did not include the current forest cover as an environmental variable but work with generalised bioclimatic regions.…”
Section: Methodsmentioning
confidence: 99%